Maintenance of automated installations - Rojas Moreno, Arturo (1999)
This paper remarks the presence of a great amount of devices and equipment employed in automated processes and power supply plants for measurement and control tasks. Relevant recommendations related with the selection of adequate and convenient human and technological resources, in order to elaborate a maintenance plan that assures its successful application, are also presented and discussed. Further, maintenance costs in automated processes are analyzed and discussed. The conclusion is that such costs tend to be smaller. An application case is discussed in order to validate the recommendations given above.